A Mobilisation Protocol in the Management of Posterior Foetal Presentations: A Multicentre Observational Pilot Study - María Belén Conesa-Ferrer; María José Martínez-Sandoval; Esther María López-Martínez; José Antonio Vera-Pérez; Isabel Baño-Piñero (Healthcare, 2026)
Background/objectives: The most common foetal malposition is the occipital posterior (OP) position, which accounts for 33.3% of malpositions occurring during labour, and the rate of dystocia reaches 95%. The aim of this study was to describe observed outcomes of a mobilisation protocol in correcting posterior foetal head positions during labour. Methods: A pilot study was conducted using a cross-sectional, multicentre methodology involving 25 pregnant women with a posterior foetal position who were asked to follow a mobilisation protocol. The women’s level of satisfaction was measured using the validated questionnaire, the Childbirth Experience Questionnaire—CEQ (Spanish version). Results: Anterior rotation was observed in 68% of cases, but in the absence of a control group, these findings cannot be distinguished from spontaneous physiological rotation, and 88% of these achieved vaginal delivery with a 95% confidence interval (76–100%). Apgar scores of ≥9 at 5 min were recorded in 100% of newborns, with an average of 9.96 with a 95% confidence interval (9.88–10.04). Women’s level of satisfaction was moderate to high, with the ‘Professional support’ and ‘Participation’ subscales standing out in particular; 100% of women noted the support they received from the midwife, and 95.24% stated that they had been involved in decision-making. Regarding perineal outcomes, no third-degree tears were recorded among women who received the protocol, and 44% of participants maintained an intact perineum. Conclusions: The protocol was feasible to implement, and anterior rotation, vaginal deliveries, favourable neonatal outcomes, and moderate-to-high maternal satisfaction were observed in this small cohort. However, future research will need to demonstrate the protocol’s efficacy through randomised controlled trials comparing the protocol with standard care.